Landscapes of Learning | Annotated Bibliography - Kingery-Page, Katie; Addo-Atuah, Kweku; Fakhraldeen, Sukaina; Hao, Shuang; King, Chelsey; Knight, Jonathan; Melvin, Rebecca; Weatherholt, Laura (Kansas State University. Dept. of Landscape Architecture/Regional & Community, 2012)
Seven master's degree candidates in the K-State Department of Landscape Architecture/Regional & Community Planning participated in a collaborative studio process leading to completion of their individual master’s reports. These graduates chose to work under the topic Landscapes of Learning . The interests of the group were broad: biophilia, access to nature for children, childhood development and special needs, ecological interpretation, participatory design, public play spaces, and landform as art. The common conversation centered around big questions: How can all children have access to nature for learning through play? What creates a rich, outdoor environment for all kinds of children and young adults? The students' annotated bibliography begins with a literature map grouping references by sub-topic and showing interrelationship between texts. The diagram is followed by a complete list of references, then the annotated entries, arranged by sub-topic. This bibliography is not intended to be exhaustive; its strength lies in connecting literature on environments for children to related themes in child development, landscape architecture and planning.
Keywords: Landscape of Learning; Schoolyard; Natural learning; Experiential learning; Nature access; Children's environments